2012
DOI: 10.1002/eat.22058
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural factors in the development of bulimia nervosa in a blind woman: A case report

Abstract: The present case underscores the need to also consider an etiological role of perceived sociocultural pressure and thin-ideal internalization in promoting body dissatisfaction and eating disorders in visually impaired women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Various research on blindness and body dissatisfaction (e.g. Vandereycken, 1986;Bemporad et al, 1989;Kocourkova et al, 2011;Simeunovic Ostojic & Hansen, 2013) agree that body dissatisfaction is as much present in the population of young women with BVI as in the sighted female population. Research findings on the extent of satisfaction among young women with blindness with their body are however contradictory, and an important reason for the contradictory findings may be the lack of a standardised instrument with which perceived BI could be assessed in this particular population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various research on blindness and body dissatisfaction (e.g. Vandereycken, 1986;Bemporad et al, 1989;Kocourkova et al, 2011;Simeunovic Ostojic & Hansen, 2013) agree that body dissatisfaction is as much present in the population of young women with BVI as in the sighted female population. Research findings on the extent of satisfaction among young women with blindness with their body are however contradictory, and an important reason for the contradictory findings may be the lack of a standardised instrument with which perceived BI could be assessed in this particular population.…”
Section: Discussionmentioning
confidence: 99%
“…Various former research findings had highlighted (e.g. Bemporad et al, 1989;Kaplan-Myrth, 2000;Kocourkova et al, 2011;Simeunovic Ostojic & Hansen, 2013;Pierce & Wardle, 1996;Yager et al, 1986) that feedback from parents and peers had a huge impact on the BI of women with blindness, and negative feedback could also lead to the construction of a distorted BI. Almost half of the participants in this research mentioned their uncertainty; not knowing to what extent they could trust feedback from important others and to what extent they should internalise it.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of body satisfaction and its role in the adjustment of females with visual impairments merits further research. However, it has been established that decreased exposure to thin-ideal images does not protect this group from experiencing body dissatisfaction (Simeunovic Ostojic & Hansen, 2013). Females with visual impairments are also exposed to sociocultural pressure associated with ideal body types and need support in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Women living with VI were initially believed to be protected from developing an eating disorder due to reduced visual exposure to cultural standards of attractiveness in the media and a limited capacity to check their appearance in mirrors and visually represent the body (Baker et al, 1998). However, case studies of women living with VI diagnosed with an eating disorder have revealed that body image disturbances can both contribute to and perpetuate the disorder (Bemporad, Hoffman, & Herzog, 1989; Dunn & Coorey, 1982; Fernández-Aranda, Crespo, Jiménez-Murcia, Krug, & Vallejo-Ruiloba, 2006; McFarlane, 1989; Sharp, 1993; Simeunovic-Ostojic & Hansen, 2013; Thomas, Weigel, Lawton, Levendusky, & Becker, 2012; Touyz, O’Sullivan, Gertler, & Beumont, 1988; Vandereycken, 1986; Yager, Hatton, & Ma, 1986). Some studies did not indicate body image disturbance as a perpetuating factor, but rather highlighted the importance of other life stressors such as developmental problems (McFarlane, 1989), susceptibility to misperceiving body size and weight (Thomas et al, 2012; Vandereycken, 1986), maladaptive stress-coping mechanisms (Fernández-Aranda et al, 2006), and issues of autonomy, independence, mobility, and plans for the future (Touyz et al, 1988).…”
Section: Women Living With Vision Impairmentmentioning
confidence: 99%